Leveraging Collaborative Governance Framework for Sustainable Stunting Reduction: An Analysis of Cross-sector Collaboration in Kabupaten Sidenreng Rappang, Indonesia - Ramlan, Pratiwi; Sukri, Phil; Abdullah, Muh.Tang; Ibrahim, Muhammad Akmal (KnE Social Sciences, 2025)
Stunting remains a critical public health challenge in Indonesia, particularly in Kabupaten Sidrap, where prevalence rates persist despite local government’s concerted efforts. This study aims to analyze cross-sector collaboration practices in stunting reduction using Emerson and Nabatchi’s collaborative governance framework. Employing a qualitative-descriptive approach, data was collected through in-depth interviews with key stakeholders, document analysis, and thematic analysis using Nvivo-12 application. Findings reveal that Kabupaten Sidrap has established a formal collaborative structure through the Tim Percepatan Penurunan Stunting (TPPS), coordinated primarily by Bappeda, with active involvement from health, family planning, education, social services, and livestock agencies. However, collaboration remains predominantly administrative, hindered by sectoral ego, limited cross-sectoral communication, inadequate data integration, and constrained budget allocation. Additionally, involvement from the private sector is minimal despite significant potential for corporate social responsibility (CSR) contributions from local industries, including egg and rice producers. Socio-cultural and economic factors exacerbate stunting risks, particularly through early marriages, traditional practices restricting early health interventions, and persistent structural poverty. Stakeholders propose enhancing collaboration through robust data integration, strengthened regulatory frameworks, improved inter-agency communication, active private sector engagement, and revitalized community-based health interventions, such as school health units (UKS) and nutrition houses (rumah gizi). This research underscores the necessity of integrating Emerson and Nabatchi’s collaborative governance principles, emphasizing principled engagement, shared motivation, and joint action capacity, to achieve sustainable stunting reduction. Policy implications highlight the need for strategic leadership, operational regulatory improvements, and comprehensive stakeholder inclusion to overcome implementation barriers and effectively address stunting in Kabupaten Sidrap.